Dietary effect of Dendrobium officinale leaves on chicken meat quality, fatty acid composition, and volatile compounds profile - Wanqiu Zhao; Yong Tian; Yunzhu Wang; Jianke Du; Li Chen; Tiantian Gu; Minquan Song; Lizhi Lu; Chongbo Sun (Food Chemistry: X, 2024)
Dendrobium officinale leaves (DOL) contain many active ingredients with various pharmacological effects, but are still ineffectively utilized. To investigate the feasibility of developing DOL as a feed additive, it is necessary to determine whether dietary supplementing DOL had any effect on meat quality and flavor. Our results showed that supplementation with DOL decreased the shear force while increased the pH and fat content in breast meat. Meat from DOL-fed chickens had higher levels of n-3 polyunsaturated fatty acids (PUFAs) and n-6 PUFAs, but lower n-6/n-3 ratios. Moreover, volatile compounds profile indicated that contents of aldehydes, including hexanal, pentanal, and heptanal, etc.), which were identified as the key volatile compounds in chicken meat, exhibited noteworthy rise in DOL intake groups. Octanal, 1-octen-3-ol, and 2-pentylfuran also contributed greatly to the meat overall aroma. These data provide a foundation for the comprehensive utilization of DOL as a feed additive with antibiotic substitution potential.